CERAI TALAK AKIBAT HUTANG PIUTANG ISTRI PERSPEKTIF MASHLAHAH MURSALAH - Arhab Ramy Ramdhani; Ahmad Ubaidi Hasbillah (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research was motivated by the large number of divorce cases in the Jombang Religious Court, which was then related to the differences in reasons for divorce cases, with this the author wanted to know and present how judges consider in deciding cases, especially focusing more on talak divorce cases because of outstanding debts. causes of reasons for breaking off a marriage bond. The purpose of this research is to find out the factors behind the legal considerations and also the considerations of the Jombang Religious Court judges in deciding divorce divorce cases due to debts and receivables in terms of the problem of murlah. The method used in this writing is empirical juridical research and uses a qualitative case approach. Meanwhile, data collection techniques use observation, interviews and documentation to explore data and then reduce it. The results of the analysis from this research show that the judge's consideration is the most important aspect in deciding or determining a decision that contains legal certainty, justice, and contains benefits for the parties concerned. Meanwhile, from the perspective of Maslahah Mursalah, giving approval for the divorce decision resulting from debts and receivables is appropriate because in this case it resulted in protracted disputes and quarrels, efforts to reconcile between the two parties have also been made but to no avail. So in this case the panel of judges approved this case because if it was not approved, it was feared that it would result in harm to both parties and bring disgrace to the family.